Sick Newborn: A Case of Critical Congenital Heart Disease - Jennifer Mitzman; Jerrid Pippin; James O'Neill (Association of American Medical Colleges, 2015)
Abstract This high-fidelity patient simulation case involves a neonate presenting to an emergency department in extremis due to a previously undetected critical congenital heart lesion, specifically, aortic coarctation. Evaluation in the emergency department reveals a tachycardic, tachypneic, hypothermic, and poorly perfused neonate who requires aggressive stabilization including oxygen, fluids, and warming. The patient will also require prostaglandin therapy and airway management. The diagnosis of critical aortic coarctation should prompt learners to involve cardiology and/or cardiothoracic surgery and admit the patient to the intensive care unit. Debriefing materials are provided to illustrate key concepts in recognition of critical congenital heart lesions as important considerations in the differential of a critically ill newborn and to stimulate discussion of the important treatment steps in resuscitation and stabilization of these children. Typical timing for this case involves approximately 20 minutes to run the patient simulation, and 20 minutes for debriefing. One program has typically used this case in conjunction with 1-2 additional pediatric cases in a 1.5-2-hour simulation session for experiential learning. The other program has used it as a single case during a pediatric workshop which includes other case based simulations, independent procedural simulations and case based discussions in a round robin format. This case was implemented in the simulation curriculum for pediatric emergency medicine fellows at the Wake Forest School of Medicine and for the emergency medicine residents at both Wake Forest and The Ohio State University College of Medicine. Time to diagnosis was quicker in the fellow group fairly consistently. Both groups recognized shock and treated it early in the scenario, with variable time to recognition of absent femoral pulses and persistent hypoxia. From there, most learners were able to move on to airway management and prostaglandin administration, though rarely learners would not meet this objective.